2013
DOI: 10.1158/0008-5472.can-13-1197
|View full text |Cite
|
Sign up to set email alerts
|

D538G Mutation in Estrogen Receptor-α: A Novel Mechanism for Acquired Endocrine Resistance in Breast Cancer

Abstract: Resistance to endocrine therapy occurs in virtually all patients with estrogen receptor a (ERa)-positive metastatic breast cancer, and is attributed to various mechanisms including loss of ERa expression, altered activity of coregulators, and cross-talk between the ERa and growth factor signaling pathways. To our knowledge, acquired mutations of the ERa have not been described as mediating endocrine resistance. Samples of 13 patients with metastatic breast cancer were analyzed for mutations in cancer-related g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

27
327
2
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 361 publications
(364 citation statements)
references
References 24 publications
27
327
2
8
Order By: Relevance
“…This finding is consistent with the known concept of tumor heterogeneity within a primary tumor and metastatic sites (25). These findings are also in accord with recent data demonstrating that acquired ER mutations can be found in liver metastatic lesions, but not pulmonary metastases within the same patient (15), and additional studies revealing that ER mutations are relatively rare in primary breast cancers but are more common after acquired resistance to endocrine therapies (12)(13)(14)16). Gene expression qRT-PCR data from the prior analysis in Fig. 1B correlated with IHC results for the metastatic sites queried in these five patients.…”
Section: Macrod2 Is Amplified In a Subset Of Tamoxifen-resistant Breastsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding is consistent with the known concept of tumor heterogeneity within a primary tumor and metastatic sites (25). These findings are also in accord with recent data demonstrating that acquired ER mutations can be found in liver metastatic lesions, but not pulmonary metastases within the same patient (15), and additional studies revealing that ER mutations are relatively rare in primary breast cancers but are more common after acquired resistance to endocrine therapies (12)(13)(14)16). Gene expression qRT-PCR data from the prior analysis in Fig. 1B correlated with IHC results for the metastatic sites queried in these five patients.…”
Section: Macrod2 Is Amplified In a Subset Of Tamoxifen-resistant Breastsupporting
confidence: 91%
“…In part, this is due to the heterogeneous nature of breast cancers, resulting in multiple mechanisms of resistance. For example, past studies have demonstrated that tamoxifen resistance is mediated by differential expression of nuclear hormone receptor coregulators (2, 3), growth factor signaling crosstalk (4-7), regulation of microRNAs (8), cyclin dependent kinases (CKDs) (9), CDK inhibitors (10,11), and more recently, acquired somatic mutations and alterations in ER (12)(13)(14)(15)(16)(17). Further insight into the molecular mediators of tamoxifen and hormone therapy resistance would have great impact on the ability to target genes and pathways that could overcome drug resistance and lead to improved clinical outcomes.…”
mentioning
confidence: 99%
“…Previous studies have reported that TP53 mutations are found in more than 80% of ctDNA samples. Mutations in the ESR1 gene are acquired in approximately 20% of breast cancers patients treated with endocrine agents and constitute a mechanism of resistance to aromatase inhibitors [38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, several studies have reported the identification of mutations in the ERα LBD in metastases of patients having undergone at least one line of endocrine treatment (Li et al . 2013, Merenbakh-Lamin et al . 2013, Robinson et al .…”
Section: Impact Of Erα Mutations Found In Endocrine Treatment-resistamentioning
confidence: 99%